The effect of different hand position on impact forces and elbow loading during the round off in female gymnastics - Farana, R.; Jandacka, D.; Uchytil, J.; Zahradnik, D.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Elbow injuries from tumbling in gymnastics present a real problem for performers. The aim of this study was to determine whether differences in hand position during the round-off influence the contact forces and elbow joint moments in female gymnasts. Five international level female gymnasts performed 10 trials of round-off from a hurdle step to back handspring with "parallel" and "T" shape hand position. Two force plates were used to determine ground reaction forces. Eight infrared cameras were employed to collect the kinematic data. T-test and effect size statistics established differences. In conclusion the "T" position of the second hand reduces vertical and anterio-posterior contact forces. Differences in joint elbow moments indicated that "T" position may prevent elbow joint complex and reduces potential of elbow injuries.